Speaking of Gods in Figure and Narrative - Westbrook, D. author. aut Link
XI, 249 p.
Keywords: Speaking of Gods analyzes the figurative-narrative creation of gods, their heavenly abodes, and behaviors, reaching back to the beginning of history in Sumer, Babylon, Egypt, Persia and Greece, and continuing through the figures and narratives of a biblical tradition that includes the Hebrew Bible, the New Testament, and the Qur'an.